Emergency Carotid Artery Stent Placement in Patients with Acute Ischemic Stroke - Imai, Keisuke (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: An effective intervention has not yet been established for patients with acute ischemic stroke who present with serious neurologic symptoms due to occlusion or a high-grade stenosis of the internal carotid artery (ICA). The aim of our retrospective study was to investigate the feasibility, safety, and efficacy of emergency carotid artery stent placement to improve neurologic symptoms and clinical outcome. METHODS: Of 896 consecutive patients with acute ischemic stroke who were admitted to our institution within 7 days of onset from July 2000 to June 2003, 17 patients (1.9%) with occlusion or a high-grade stenosis of the ICA underwent emergency carotid artery stent placement. We reviewed their records for neurologic outcome, per the National Institutes of Health Stroke Scale (NIHSS) score, before and at 7 days after stent placement; clinical outcome, per the modified Rankin Scale score (mRS), at 90 days; frequency of procedure-related complications within 30 days; and recurrence rate of ipsilateral ischemic stroke within 90 days. RESULTS: Carotid lesions were dilated completely in all patients. Median NIHSS scores before emergency stent placement and at 7 days were 12 and 5, respectively, showing significant improvement (P < .01, Wilcoxon rank sum test). Ten patients (59%) had favorable outcomes (mRS score 0–1) at 90 days. Irreversible complications occurred in two patients (12%): distal embolism in one and intracerebral hemorrhage in the other. No ipsilateral ischemic stroke recurred. CONCLUSION: Emergency carotid artery stent placement can improve the 7-day neurologic outcome and may improve the 90-day clinical outcome in selected patients with ischemic stroke.